2019
DOI: 10.1093/wber/lhz047
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Age Regulation and Child Labor: New Evidence from Brazil

Abstract: This study presents new evidence on the effects of minimum age regulations obtained from a natural experiment. In 1998, a constitutional reform in Brazil changed the minimum working age from 14 to 16. The reform was the legislative counterpart of a broad set of measures taken by a government strongly committed to eliminating child labor. This article investigates the role of the minimum working age in this context. The setting allows for improvements upon past approaches based on comparing employment rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…Psacharopoulos' (1997) analysis revealed significant partici-90 pation in the labour market among children who should be prevented from it by compulsory education or working age legislation. Similar evidence was found in Brazil by Bargain and Boutin (2017) and in data from 59 countries including Venezuela, the Dominican Republic and Bolivia by Edmonds and Shrestha (2012). Legislation often fails in eliminating child labour in its entirety as legislation does not cover the entire economy or only applies to specific activities or sectors (Boockmann, 2010).…”
Section: Literature Reviewsupporting
confidence: 66%
See 1 more Smart Citation
“…Psacharopoulos' (1997) analysis revealed significant partici-90 pation in the labour market among children who should be prevented from it by compulsory education or working age legislation. Similar evidence was found in Brazil by Bargain and Boutin (2017) and in data from 59 countries including Venezuela, the Dominican Republic and Bolivia by Edmonds and Shrestha (2012). Legislation often fails in eliminating child labour in its entirety as legislation does not cover the entire economy or only applies to specific activities or sectors (Boockmann, 2010).…”
Section: Literature Reviewsupporting
confidence: 66%
“…In addition the prohibition of child labour (through minimum legal working age laws) is rarely applied uniformly across all activities. Thus, it may in fact merely lead to the reallocation of child labour into unregulated sectors such as family businesses or work happening inside the household where these laws do not apply or are even more difficult to enforce (Bargain & Boutin, 2017). Using a two-sector model of employment in which legislation completely eliminates child labour, Basu (2005) found that a ban via minimum age legislation in this model instead pushed children into unregulated work.…”
Section: Household Labourmentioning
confidence: 99%
“…The benefits of education can be different for individuals and society (Bargain & Boutin, 2021). Most contemporary researchers in economics are interested in child labor because of the impact of child labor on human capital accumulation.…”
Section: Cost Of Education and Child Labourmentioning
confidence: 99%
“…We are aware of only five studies that investigate the e ects of an increase in the minimum employment age in developing countries: the aforementioned Piza and Souza (2016) and Bargain and Boutin (2021), Bharadwaj et al (2020), Kozhaya andMartinez Flores (2022), andEdmonds andShrestha (2012). Bharadwaj et al (2020) investigate the impact of the child labor ban in India and find that the law increased child labor in the informal sector and reduced wages.…”
Section: Related Literaturementioning
confidence: 99%
“…In states with above-median inspection rates, the authors detect a 4 percentage points decrease in child labor. Even though Piza and Souza (2016) and Bargain and Boutin (2021) work on the 1999 wave of the Brazilian Household Survey (PNAD), it is important to describe the key di erences between the two studies.…”
Section: Related Literaturementioning
confidence: 99%